PENGGUNAAN MULSA PLASTIK SEBAGAI UPAYA KONSERVASI LAHAN UNTUK MENJAGA STABILITAS SIFAT FISIKA DAN KIMIA TANAH - Sudartini, Tini; Fitria, Anita Dwy; Yulianto, Yanto; Undang, Undang (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Low nutrient availability and high soil bulk density are caused by the loss of fertile soil particles due to the kinetic energy of rain. Land management that does not apply conservation principles such as soil covering is one of the factors causing this to happen. This research was conducted to determine the impact of using plastic mulch as one of conservation actions. This research was conducted at the experimental field University of Siliwangi, Mugarsari. Soil samples were taken from mulched and without mulch lands as treatments. Soil samples were collected at 0-10 and 10-30 cm soil depths. Soil samples were taken to analyze the chemical properties of the soils (i.e., pH H2O, organic C, total N, available P, exchangeable K, Ca, Mg, Na) and physical properties (i.e., soil bulk density, porosity, water content, and texture). The results showed that the use of mulch had a significant effect (p<0.05) on pH H2O, organic C, total N, available P, exchangeable K, exchangeable Ca, bulk density, and water content. The results of the correlation showed that increasing organic C in mulched land had an effect on decreasing BD (r = -0.739). In addition, the organic C increased soil porosity (r = 0.612). Meanwhile, soil depth had no effect (p>0.05) on soil chemical and physical properties.